Effects of temperature on responses to anoxia and oxygen reperfusion in Drosophila melanogaster - Schilman, Pablo Ernesto (2011)
Insects in general, and Drosophila in particular, are much more capable of surviving anoxia than vertebrates, and the mechanisms involved are of considerable biomedical and ecological interest. Temperature is likely to strongly affect both the rates of damage occurring in anoxia and the recovery processes in normoxia, but as yet there is no information on the effect of this crucial variable on recovery rates from anoxia in any animal. We studied the effects of temperature, and thus indirectly of metabolic flux rates, on survival and recovery times of individual male Drosophila melanogaster following anoxia and O2 reperfusion. Individual flies were reared at 25° and exposed to an anoxic period of 7.5, 25, 42.5 or 60?min at 20, 25 or 30°. Before, during and after anoxic exposure the flies' metabolic rates (MRs), rates of water loss and activity indices were recorded. Temperature strongly affected the MR of the flies, with a Q10 of 2.21. Temperature did not affect the slope of the relationship between time to recovery and duration of anoxic exposure, suggesting that thermal effects on damage and repair rates were similar. However, the intercept of that relationship was significantly lower (i.e. recovery was most rapid) at 25°, which was the rearing temperature. When temperatures during exposure to anoxia and during recovery were switched, recovery times matched those predicted from a model in which the accumulation and clearance of metabolic end-products share a similar dependence on temperature.